2018
DOI: 10.1111/bcp.13768
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient toxicology services improve resource utilization for intoxicated patients: a systematic review

Abstract: Aims Presentations of intoxicated patients to hospital are frequent and increasing. We aimed to review the existing evidence that the presence of inpatient clinical toxicology services reduces use of resources without impacting on the care of these patients. Methods We conducted a literature search using the Cochrane Library, PubMed, and Embase for articles that measured length of stay (and other outcomes) for the target population, with toxicology services as an intervention. The articles were reviewed with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Medical toxicologist advice can guide use of resources and interventions, including consulting on specific, complex interventions such as antidote use, decontamination strategies and extracorporeal elimination, 28 while also avoiding unnecessary, costly and even harmful interventions. 9,13 A recent study from the Netherlands found that 23% of hospital-admitted poisoning patients were retrospectively found not to require any active intervention. 29 Medical toxicologists can also advise on escalation of care if tertiary care in a larger facility is needed, or if other specialist input ought to be obtained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical toxicologist advice can guide use of resources and interventions, including consulting on specific, complex interventions such as antidote use, decontamination strategies and extracorporeal elimination, 28 while also avoiding unnecessary, costly and even harmful interventions. 9,13 A recent study from the Netherlands found that 23% of hospital-admitted poisoning patients were retrospectively found not to require any active intervention. 29 Medical toxicologists can also advise on escalation of care if tertiary care in a larger facility is needed, or if other specialist input ought to be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…7 In various settings and across multiple countries, consultations with poisons centres and involvement of medical toxicologists in patient care has been associated with a variety of benefits including decreased length of stay, reduced healthcare costs and reduced resource utilisation. [8][9][10][11][12][13] The National Poisons Centre (NPC) operates with 15 full-time equivalent staff roles, two of which are medical toxicologist roles. The toxicologist roles are currently filled by registered, vocationally certified emergency medicine specialists who also have formal training and certifications in medical toxicol-ogy from overseas.…”
Section: Specialist Medical Toxicologist Consultations Provided By Th...mentioning
confidence: 99%
“…Inpatient clinical toxicology units are an established part of the Australian healthcare system and bring many advantages to the care of poisoned patients, reducing hospital length of stay and making more efficient use of resources [1,2]. In addition to clinical care, many toxicology units routinely collect inpatient data providing high quality information on patterns of toxin exposure, patient morbidity and mortality, and treatments used [3].…”
Section: Introductionmentioning
confidence: 99%